Lighthouse Jetty, Trinidad. - (:unkn) unknown (Davidson-Todd. Ltd., 2011)
A picture of the picturesque Port of Spain harbour, from the sea, featuring ships docked at the St. Vincent Jetty with the Lighthouse and Customs Office, public buildings and mountains in the background. You can also see people on the jetty.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Boats and boating--Trinidad and Tobago; Lighthouses--Trinidad and Tobago; Harbors--Trinidad and Tobago; Customhouses--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Public buildings--Trinidad and Tobago; Docks--Trinidad and Tobago; Jetties--Trinidad and Tobago; [1910]; Ships--Trinidad and Tobago; Ports of entry--Trinidad and Tobago; Mountains--Trinidad and Tobago